Pelatihan Penggunaan Artificial Intelligence (AI) dalam Penulisan Folklor Berbahasa Inggris Bagi Siswa SMA Negeri 9 Denpasar: Penelitian - Dewa Ayu Kadek Claria; I Gusti Ngurah Adi Rajistha; Ni Made Suwendri; Dewa Ayu Agung Dyah Ratnaduhita; Ni Putu Aleychia Resnanda Dania Surya Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The use of artificial Intelligence technology in education is very common today, especially as a media for learning. In the current era of technological developments, the entire academic community needs to respond to these changes positively by utilizing technology, known as AI to enhance learning effectiveness. SMA Negeri 9 Denpasar is one of the schools that follows the development of the era by integrating the use of AI in English language learning, especially in writing Folklore. Inappropriate use of technology can lead to laziness, but if it used properly, it can increase student creativity. The results of the training showed an increase in student abilities both in mastering new English vocabulary and understanding of cultural values contained in folklore by using AI.